HUBUNGAN ANTARA KECERDASAN LOGIS MATEMATIKA DAN KEDISIPLINAN BELAJAR SISWA KELAS V SD NEGERI 1 PAGAR AIR KABUPATEN ACEH BESAR - Fauzi Fauzi.; Monawati Monawati. (Universitas Syiah Kuala, 2018)
This study aims to determine whether there is a significant relationship between mathematical logical intelligence with the discipline of students in grade fifthElementary School Negeri 1 Pagar Air Kabupaten Aceh Besar. To answer the purpose of this study, researchers used a quantitative approach to the type of associative research. The sample in this research is 40 students in gradefifthof Elementary School Negeri 1 Pagar Air. Data collection techniques used are tests and questionnaires. Data analysis technique used is simple regression analysis. Based on the results of data analysis shows that there is a positive and significant relationship between mathematical logical intelligence with the discipline of students in grade fifthElementary School Negeri 1 Pagar Air. This is indicated by the value of Fcount Ftable at the 5% significance level of 5.98 4.10 and the regression equation Ŷ = 76.02 + 0.99X which can predict the rise and fall of students' learning discipline. The magnitude of the influence of mathematical logical intelligence with student learning discipline can be seen from the value of rxy = 0.370, rcount bigger than rtable at 5% significance level that is 0.370 0.320, it means mathematical logical intelligence contributes 13.69%. Thus it can be concluded that there is a significant relationship between mathematical logical intelligence with the discipline of students in grade fifthElementary School Negeri 1 Pagar Air Kabupaten Aceh Besar.